(untitled) (Research, Society and Development, 2025)
The article aims to analyze freedom as a personality right through a theoretical, bibliographic, deductive, and hermeneutic-critical approach. Based on classical and modern philosophical foundations, the study demonstrates how freedom evolves from an ethical-political ideal to a structuring legal value within contemporary constitutionalism. Through a comparative perspective, it analyzes the development of Western constitutional traditions and the mechanisms by which freedom becomes a fundamental right, highlighting the insufficiency of its merely negative conception and the need for material guarantees to ensure its concrete realization. In the Brazilian context, the 1988 Constitution inaugurates a personalist shift by establishing human dignity as a foundational principle, thereby radiating freedom throughout the entire legal system, including private relations. The civil-constitutional analysis reveals that protecting freedom requires both preventive and reparatory measures, as well as an interpretive framework committed to overcoming historical forms of suppression. The study further demonstrates that cases such as Gomes Lund and Herzog, decided by the Inter-American Court of Human Rights, reinforce the duty of memory and underscore the centrality of freedom within transitional justice, a necessary condition for strengthening the Democratic Rule of Law. It concludes that freedom, as a personality right, constitutes a legal power of subjective self-constitution expressed in existential autonomy, psychic inviolability, and personal development. Its effectiveness depends on institutional practices, public policies, and constitutional interpretation guided by human dignity.